Trend analysis of leprosy in Morocco between 2000 and 2017: Evidence on the single dose rifampicin chemoprophylaxis. - Ibtissam Khoudri; Zainab Elyoussfi; Yassine Mourchid; Mohammed Youbi; Nada Bennani Mechita; Redouane Abouqal; Abderrahmane Maaroufi (Public Library of Science (PLoS), 2018)
BACKGROUND:Morocco has achieved the goal of leprosy elimination as a public health problem several years ago (less than 1 case/ 10 000 habitant). The aim of this study was to analyze trends of leprosy detection during the last 17 years taking into consideration the implementation of single dose rifampicin chemoprophylaxis (SDRC) started in 2012. METHODOLOGY:Time series of leprosy cases detected at national level between 2000 and 2017. Variable collected for each year were leprosy per 100000 H, age category, gender, origin, regions, grade of disabilities and clinical forms. The detection time series was assessed by Joinpoint Regression Analysis. Annual percentage changes (APCs) were estimated to identify the years (joinpoint) when significant changes occurred in the trend. We therefore examined trends in leprosy detection according to epidemiological variables. FINDINGS:Joinpoint regression showed a reduction in the detection rate between 2000 and 2017. The APC for the period 2012-2017 (-16.83, 95% CI: -29.2 to -2.3, p <0.05) was more pronounced than that of the previous period 2000-2012 (- 4.68, 95% CI: -7.3 to -2.0, p <0.05); with a significant break in the same joinpoint year SDRC implementation. In stratified analysis, case detection decreased, but not significantly, after the joinpoint years in men, children, multi-bacillary cases, grade 0-1 disabilities, rural and urban cases and in ten regions. CONCLUSIONS:Leprosy detection was declining over years with a significant reduction by 16% per year from 2012 to 2017. SDRC may reduce leprosy detection over the years following its administration.